Bacteria in atmospheric waters: Detection, characteristics and implications - Wei Hu; Niu, Hongya; Murata, Kotaro; Zhijun Wu; Min Hu; Kojima, Tomoko; Zhang, Daizhou (ATMOSPHERIC ENVIRONMENT, 2018)
In this review paper, we synthesize the current knowledges about bacteria in atmospheric waters, e.g., cloud, fog, rain, and snow, most of which were obtained very recently. First, we briefly describe the importance of bacteria in atmospheric waters, i.e., the essentiality of studying bacteria In atmospheric waters in understanding aerosol-cloud-precipitation-climate interactions in the Earth system. Next, approaches to collect atmospheric water samples for the detection of bacteria and methods to identify the bacteria are summarized and compared. Then the available data on the abundance, viability and community composition of bacteria in atmospheric waters are summarized. The average bacterial concentration in cloud water was usually on the order 10(4)-10(5) cells mL(-1), while that in precipitation on the order 10(3)-10(4) cells mL(-1). Most of the bacteria were viable or metabolically active. Their community composition was highly diverse and differed at various sites. Factors potentially influencing the bacteria, e.g., air pollution levels and sources, meteorological conditions, seasonal effect, and physicochemical properties of atmospheric waters, are described. After that, the implications of bacteria present in atmospheric waters, including their effect on nucleation in clouds, atmospheric chemistry, ecosystems and public health, are briefly discussed. Finally, based on the current knowledges on bacteria in atmospheric waters, which in fact remains largely unknown, we give perspectives that should be paid attention to in future studies.
Keywords: Abundance; atmospheric chemistry; Atmospheric water; Bacteria; Community composition; Ice nuclel; Viability